RESPONSE: FACTORS RELATED TO THE SUCCESS OF THE TREATMENT PROGRAM OF MULTIDRUG-RESISTANT TUBERCULOSIS IN POLYCLINIC OF MDR-TB OF THE GENERAL HOSPITAL OF UNDATA PALU, INDONESIA - Asyary, Al (Public Health of Indonesia, 2018)
None